Large and small muscles in resistance training: Is it time for a better definition? - Ribeiro, A. S.; Schoenfeld, B. J. (Strength and Conditioning Journal, 2017)
Many studies have misapplied the definition of muscle volume with respect to classifying muscles as "small" or "large." given frequent misapplication of the terms, we propose that they should be classified simply as multijoint or single-joint exercises. A viable alternative classification would be compound exercises or isolation exercises.